2012
DOI: 10.1073/pnas.1115621109
|View full text |Cite
|
Sign up to set email alerts
|

Bifidobacterial surface-exopolysaccharide facilitates commensal-host interaction through immune modulation and pathogen protection

Abstract: Bifidobacteria comprise a significant proportion of the human gut microbiota. Several bifidobacterial strains are currently used as therapeutic interventions, claiming various health benefits by acting as probiotics. However, the precise mechanisms by which they maintain habitation within their host and consequently provide these benefits are not fully understood. Here we show that Bifidobacterium breve UCC2003 produces a cell surface-associated exopolysaccharide (EPS), the biosynthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
429
3
6

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 469 publications
(464 citation statements)
references
References 23 publications
15
429
3
6
Order By: Relevance
“…Further investigation is required to provide mechanistic correlation, but we hypothesise that bifidobacteria may potentially modulate foetal immune development at the very first stages of life. and links to specific bifidobacteria molecules [40,41], such as pili and exopolysaccharide (EPS), on immune responses [5,42,43]. However, it is apparent that the bifidobacteria-immune field requires a greater number of investigations detailing key mechanistic targets and pathways in different immune compartments and immune cell types.…”
Section: Effects Of Bifidobacteria On the Immune Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Further investigation is required to provide mechanistic correlation, but we hypothesise that bifidobacteria may potentially modulate foetal immune development at the very first stages of life. and links to specific bifidobacteria molecules [40,41], such as pili and exopolysaccharide (EPS), on immune responses [5,42,43]. However, it is apparent that the bifidobacteria-immune field requires a greater number of investigations detailing key mechanistic targets and pathways in different immune compartments and immune cell types.…”
Section: Effects Of Bifidobacteria On the Immune Systemmentioning
confidence: 99%
“…infantis 35624 to modulate innate immune cells, such as neutrophils, macrophages, and peripheral monocytes [5,43]. An EPS deletion mutant in B. breve UCC2003 induced more pro-inflammatory cytokine secretion from splenocytes and also increased the number of Ly6G + neutrophils, F4/80 + macrophages, DX5 + /CD3 + NK cells, and CD19 + B cells in the spleen of treated mice compared with mice treated with the wild-type strain [5]. Similarly, an EPS deletion mutant of B. longum subsp.…”
Section: Other Cells Typesmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we showed that strain HTF-F produces an extracellular polymeric matrix (EPM) that might provide an advantage to colonization in vivo through intercellular aggregation and biofilm formation. As bacterial EPMs are common components of biofilm matrices and have been previously shown to have immunomodulatory effects [8][9][10], we tested the EPM of strain HTF-F for its potential anti-inflammatory effects in the DSS colitis model. Additionally, the immunomodulatory effects of the EPM were investigated using immature dendritic cells derived ex vivo from human monocytes and mouse bone marrow cells.…”
Section: Introductionmentioning
confidence: 99%
“…1) In some studies, consumption of specific bifidobacteria has been shown to be associated with immune modulation, 2) protection against pathogens, 2,3) and anti-aging effects. 4) Therefore, several Bifidobacterium strains are commonly used as probiotics.…”
mentioning
confidence: 99%